(untitled) (Journal of Science & Technology, 2021)
In the realm of property and casualty insurance, claims processing efficiency stands as a pivotal factor in ensuring customer satisfaction, operational excellence, and financial stability. This research delves into the transformative potential of data analytics in enhancing claims processing efficiency within this domain. By leveraging advanced analytics techniques, such as real-time data processing, machine learning algorithms, and predictive modeling, insurers can streamline various facets of the claims journey, including triaging, fraud detection, and settlement optimization. This paper examines the methodologies, technologies, and best practices involved in harnessing data analytics to optimize claims processing in property and casualty insurance, offering insights into how insurers can leverage data-driven approaches to achieve operational excellence and deliver enhanced value to policyholders.